Prosedur Penerjemahan Kategori Istilah Budaya Ekologi Pada Novel Laskar Pelangi Beserta Terjemahannya Niji No Shounen Tachi - Mertha Harimbawa, I Dewa Made; Oeinada, I Gede; Wiriani, Ni Made (Humanis; Volume 17. No. 2. Nopember 2016, 2017)
This research is entitled “Procedure of Translation of Ecology Cultural Terms in Laskar Pelangi Novel With Japanese Translated Niji No Shounen Tachi”. This research discuss about procedure of translation and ecology cultural terms in Laskar Pelangi novel. The main theory used in the analysis  were procedure of translation Theory by Newmark (1988), and ecology cultural terms by Newmark (1988). The analysis in this paper shows that in all 54 datas, there are 5 kind of sub category of ecology cultural terms and 5 kind of procedur of translation in Laskar Pelangi novel. From all that data, Cultural Equivalent is mostly use to translating ecology cultural terms than other procedure. The ecology cultural terms are contained in sourch languange have been translated in the target languange.
Keywords: Translated, ecology cultural terms, procedure of translation